Improving Digital Health Readiness Among Community Health Cadres Through The AHHEM Model - Deny Nugroho Triwibowo; Rian Ardianto; Rosyid Ridlo Alhakim; Hadi Jayusman; Iis Setiawan Mangkunegara; Atina Salamah (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Digital health transformation requires human resource readiness, particularly community health cadres who serve as the frontline of community-based services. However, limited digital literacy and reliance on manual record-keeping present significant challenges in supporting digital health system implementation. This community service program aims to enhance the understanding and readiness of health cadres in facing digital health transformation. The activity was conducted in Karangrau Village, Banyumas Regency, involving 25 participants consisting of one village midwife and 24 health cadres. The method applied was the Adaptive Hybrid Health Empowerment Monitoring Model (AHHEM), integrating assessment, harmonization, health literacy, empowerment, and evaluation over a one-day intervention. The evaluation employed a pre-test and post-test design to measure cognitive shifts. The results showed a substantial improvement in participants’ understanding, increasing from 53% in the pre-test to 89% in the post-test. Participants also demonstrated improved readiness in understanding the role of digital technology and health information systems. The main strength of this approach lies in its focus on human readiness rather than solely on technological implementation. Therefore, this program strengthens cadre capacity and supports the sustainable implementation of digital health transformation at the community level.